Quantifying the direct economic damage caused by the impact of climate change in Asia Pacific Region - Safi, Safwan Mahmood (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2022.